Pump-induced lensing effects in diode pumped Alexandrite lasers - Tawy,G; Wang,J; Damzen,M (Optics Express, 2019)
It is essential to understand the pump-induced lensing and aberration effects in solid-state lasers, such as Alexandrite, since these set limits on laser power scaling whilst maintaininghigh spatial TEM00beam quality. In this work, we present direct wavefront measurements ofpump-induced lensing and spherical aberration using a Shack-Hartmann wavefront sensor, for thefirst time, in a diode-pumped Alexandrite laser, and under both non-lasing and lasing conditions.The lens dioptric power is found to be weakly sub-linear with respect to the absorbed pumppower, and under lasing, the lensing power is observed to decrease to60 %of its non-lasingvalue. The results are inconsistent with a thermal lens model but a fuller theoretical formulationis made of a combined thermal and population lens model giving good quantitative agreementto the observed pump power dependence of the induced-lensing under non-lasing conditionsand the reduced lensing under lasing conditions. The deduced value for the difference inexcited to ground state polarizability is consistent with prior measurement estimates for otherchromium-doped gain media. The finding of this paper provide new insight into pump-inducedlensing in Alexandrite and also provides a basis for a fast saturable population lens mechanism toaccount for self-Q-switching observed recently in Alexandrite laser systems.